Synergistic effect of Wharton's jelly-derived mesenchymal stem cells and insulin on Schwann cell proliferation in Charcot-Marie-Tooth disease type 1A treatment - Shin Ji Oh; Hyeongseop Kim; Sang Eon Park; Jeong Hee Kim; Yong Jun Kim; Suk-joo Choi; Soo-young Oh; Hong Bae Jeon; Jong Wook Chang (Neurobiology of Disease)
Charcot-Marie-Tooth disease type 1A (CMT1A) is a demyelinating disease caused by PMP22 duplication and an exceedingly rare hereditary peripheral neuropathy, with an incidence of 1 in 2500. Currently, no cure exists for CMT1A; however, various therapeutic approaches are under development. Considering the known therapeutic effects of mesenchymal stem cells (MSCs) and the relation of blood sugar levels with nerve damage in CMT, this study aimed to confirm the therapeutic effects of MSCs and insulin on CMT, using both in-vitro and in-vivo models. CMT1A in-vitro models were exposed to Wharton's jelly-derived MSCs (WJ-MSCs) or insulin, and the resulting proliferation changes were measured. CMT1A mice were treated with WJ-MSCs or insulin, and their phenotypic changes were observed. We observed improvements in myelination of Schwann cells in vitro and motor function in vivo. Insulin also showed therapeutic efficacy by promoting Schwann cell proliferation. Furthermore, combination therapy using insulin and WJ-MSCs was more effective than WJ-MSCs or insulin alone. Insulin promoted the proliferation of Schwann cells and WJ-MSCs through activation of the ATK and PI3K-MAPK signaling pathways. Overall, this study is the first to confirm the therapeutic efficacy of WJ-MSCs and insulin in CMT1A, and their synergistic effect without causing insulin resistance.